A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay - Espejo, Yolanda M. G. Piñanez; Kochalka, John A.; Barrett, Bolívar R. Garcete (Zootaxa, 2019)
The family Gnaphosidae consist of 158 genera and 2530 species worldwide. In South America there are 35 genera (World Spider Catalog 2019) considering Apopyllus Platnick & Shadab, 1984, a small genus of ground hunting spiders (Cardoso et al. 2011) that includes ten American species, of which eight have been recorded from southern South America. Their known distribution ranges from southern Mexico through Colombia, Bolivia, Perú, Chile, Brazil and Argentina (World Spider Catalog 2019). In Paraguay, the genus was first mentioned in an invertebrate checklist (see Kochalka et al. 1996). First studies on the genus and its taxonomic placement were made by Platnick & Shadab (1984), and more recently a revision of the genus was undertaken by Azevedo et al. (2016), including four new Brazilian species. Even though the external appearance of Apopyllus is similar to other gnaphosids, specifically taking into consideration the Echemus group, spiders with plain colored abdomens, sometimes presenting chevrons in the opisthosoma, and with developed scutum in males (Murphy 2007), females and males can be differentiated by the more elaborated and intricated genitalia structures (see Azevededo et al. 2016). Apopyllus is most similar to Apodrassodes Vellard, 1924 both having a similar elongate embolus (Fig. 3e) and a membranous tegular extension (Fig. 3d) (Platnick & Shadab 1984), and to the genera Nopyllus Ott, 2014, but differ from the later by the presence of a scutum (Fig. 3a) in males and by the presence of a median apophysis (Fig. 3e) on the bulb (Ott, 2014).